Probiotics and Bacteriocins Against SARS-CoV-2: Therapeutic Frontiers and Mechanistic Insights - Simeng Sun; Xinyue Guo; Simeng Liu; Shuhong Wu; Lei Ma; Hongru Yang (Probiotics and Antimicrobial Proteins, 2026)

Two-step interfacial polymerization for bilayer polyamide membranes with a gradient-density structure and enhanced desalination performance - Simeng Wang; Yi Wei; Mengqi Ma; Kaiyu He; Bo Wang (Desalination, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Response of organic matter decomposition and nitrogen transformation in surface sediment to Hyriopsis cumingii bioturbation - Zhaoxing Wu; Zhaohui Tian; Junfeng Ma; Simeng Chen; Shaogang Xu; Hongda Liu; Yan Chen (Journal of Cleaner Production, 2026)

Novel quantitative method of reactive losses of ambient VOCs coupling chemical transport model simulation with receptor measurement - Yao Gu; Baoshuang Liu; Simeng Ma; Zhongwei Luo; Jinqiu Zhang; Danni Liang; Yafei Li; Yufen Zhang; Yinchang Feng (Journal of Hazardous Materials, 2025)

Quantitative source apportionment of surface ozone in Liaoning Province, China, under the Asian summer monsoon background - Ningwei Liu; Simeng Ma; Kun Wang; Sen Yang; Zhigang Zhang (Atmospheric Pollution Research, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Drivers of civil aviation emissions in China: Considering spatial heterogeneity and interdependence - Simeng Ma; Wenhui Zheng; Bo Han; Zhiqiang Deng; Jinglei Yu; Jingbo Zhao; Chen Zhang; Jian Yu; Philip K. Hopke (Environmental Pollution, 2025)

Plant polyphenols as natural bioactives for alleviating lipid metabolism disorder: Mechanisms and application challenges - Haiying Wei; Jinsheng Rui; Xinke Yan; Ruyan Xu; Simeng Chen; Baiming Zhang; Lei Wang; Zhisong Zhang; Chengwen Zhu; Mengtao Ma; Huining Xiao (Food Research International, 2025)

Exploring emission spatiotemporal pattern and potential reduction capacity in China's aviation sector: Flight trajectory optimization perspective - Simeng Ma; Xuan Wang; Bo Han; Jingbo Zhao; Zhongyi Guan; Jinlong Wang; Yufen Zhang; Baoshuang Liu; Jian Yu; Yinchang Feng; Philip K. Hopke (Science of The Total Environment, 2024)

Exposure to volatile organic compounds and growth indicators in adolescents: Unveiling the association and potential intervention strategies - Jingyi Ren; Xiaoya Sun; Zhenao Zhang; Huanting Pei; Yadong Zhang; Rui Wen; Simeng Qiao; Zidan Wang; Weican Zhang; Jinshi Zuo; Yuxia Ma (Journal of Hazardous Materials, 2024)

Multi-model predictive control strategy for path-following of unmanned surface vehicles in wide-range speed variations - Yingkai Ma; Zhilin Liu; Ting Wang; Simeng Song; Jing Xiang; Xiaoyue Zhang (Ocean Engineering, 2024)

5-Methoxytryptophan ameliorates endotoxin-induced acute lung injury in vivo and in vitro by inhibiting NLRP3 inflammasome-mediated pyroptosis through the Nrf2/HO-1 signaling pathway - Yang Ma; Zhixue Wang; Xiaoyang Wu; Zijian Ma; Jia Shi; Simeng He; Shaona Li; Xiangyun Li; Xiangkun Li; Yan Li; Jianbo Yu (Inflammation Research, 2023)

Comparative analysis of nitrate evolution patterns during pollution episodes: Method development and results from Tianjin, China - Yafei Li; Yan Han; Simeng Ma; Yufen Zhang; Haoqi Wang; Jingyi Yang; Lu Yao; Xiaohui Bi; Jianhui Wu; Yinchang Feng (Science of The Total Environment, 2023)

ALOS-Based USV Path-Following Control with Obstacle Avoidance Strategy - Zhilin Liu; Simeng Song; Shouzheng Yuan; Yingkai Ma; Zongxun Yao (Journal of Marine Science and Engineering, 2022)
Path following and obstacle avoidances are used in heading control and path replanning for unmanned surface vessels (USVs), which have attracted the interest of many researchers over the years. This paper investigates the path-following and obstacle avoidance problems for USVs. First, on the basis of the current position and desired path, an adaptive line-of-sight (ALOS) algorithm is used to obtain the desired heading angle, and the sideslip angle compensation is considered. Then, to ensure that the USV follows the desired path. Model predictive control (MPC) is used to reduce the lateral error. The event-triggered mechanism (ETM) strategy is utilized to reduce the computational cost of MPC. Moreover, to obtain accurate state quantities in real time, a linear extended state observer (LESO) is used to counteract the effects of external disturbances and the nonlinear term of the model. Furthermore, an improved obstacle avoidance algorithm based on the geometric relationship is proposed. This method can better ensure USV navigation safety and reduce consumption and computation. Lastly, multiple simulation experiments illustrate that the algorithm improves the path-following capability and security and ensures smooth input changes by setting input constraints. Therefore, the designed controller has better feasibility and robustness.

Metabolomics changes in brain-gut axis after unpredictable chronic mild stress - Qiuyue Xu; Mingchen Jiang; Simeng Gu; Xunle Zhang; Guangkui Feng; Xianjun Ma; Shijun Xu; Erxi Wu; Jason H Huang; Fushun Wang (Psychopharmacology, 2022)
Background Major depressive disorder is a leading cause of disability worldwide, affecting up to 17 % of the general population. The neural mechanisms of depression, however, are yet to be uncovered. Recently, attention has been drawn to the effects of dysfunctional brain-gut axis on depression, and many substances have been suggested to be involved in the communication between the gut and brain, such as ghrelin. Methods We herein systematically examined the changes of metabolomics after unpredictable chronic mild stress (UCMS)–induced depression-like behaviors in rats and compared the altered metabolites in the hippocampus and jejunum samples. Results Our results show that many metabolites significantly changed with UCMS both in the hippocampus and jejunum, such as L-glutamine, L-tyrosine, hydroxylamine, and 3-phosphoglyceric acid. Further studies suggested that these changes are the reasons for anxiety-like behaviors and depression-like behaviors in UCMS rats and also are the reasons for hippocampal neural plasticity. Conclusions Coexistence of brain and gut metabolic changes in UCMS-induced depressive behavior in rats suggests a possible role of brain-gut axis in depression. This study provides insights into the neurobiology of depression.